Usability Testing (International Journal of Engineering and Computer Science, 2014)
Usability Testing is the process by which the human-computer interaction characteristics of a system are measured, and weaknesses are identified for correction. It is a process by which products are tested by those who will use the system. The need for a Usability Testing is someone who is a user of the design (who acts like a user), something to test (a design in any state of completion), and someplace where the user and design can meet and can be observed. Gathering Usability Testing Requirements is different from Functional Test Requirements because they are much loosely defined. Often many of these requirements are implicitly stated and requirements vary depending on the Business Domain of the system and its Target Users. Studying the user work profile could help the Test Team decide on how Usability Testing needs to be done. Usability Testing is a kind of a Quality Testing that assesses how easily the User Interfaces can be used.